2009
DOI: 10.1017/s002222670999003x
|View full text |Cite
|
Sign up to set email alerts
|

Clausal parentheticals, intonational phrasing, and prosodic theory

Abstract: This paper investigates the intonational phrasing of three types of parenthetical insertions – non-restrictive relative clauses (NRRCs), full sentences, and comment clauses (CCs) – in actual spoken language. It draws on a large set of data from a corpus of spoken British English. Its aim is twofold: first, it evaluates the correctness of previous claims about the intonational phrasing of parentheticals, specifically the assumption that parentheticals are phrased in a separate intonation domain; second, it disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 67 publications
4
78
0
10
Order By: Relevance
“…This is not what we normally perceive for the demonstrative in CLD. However, it is convincingly shown by Dehé (2009) that the phonological behaviour of parentheticals does not always match the syntactic boundaries. In particular, weak/short parentheticals or first elements of longer parentheticals can be prosodically integrated with the surrounding material (an example is a parenthetical like denk ik 'I think').…”
Section: Syntactic Analysis: Parenthesis At Different Levelsmentioning
confidence: 99%
“…This is not what we normally perceive for the demonstrative in CLD. However, it is convincingly shown by Dehé (2009) that the phonological behaviour of parentheticals does not always match the syntactic boundaries. In particular, weak/short parentheticals or first elements of longer parentheticals can be prosodically integrated with the surrounding material (an example is a parenthetical like denk ik 'I think').…”
Section: Syntactic Analysis: Parenthesis At Different Levelsmentioning
confidence: 99%
“…As research by Dehé andWichmann (2010a, 2010b) has shown for English comment clauses and matrix clauses like I think and I believe, prosody can be key in distinguishing the various functional profiles that these expressions may have; depending on their prosodic profile, they may function as matrix clauses, comment clauses or discourse markers and speakers use distinct prosodic patterns to disambiguate these functions and their associated meanings. More sophisticated research into the prosody of schij nenconstructions as well as parentheticals and particles in Dutch would help shed more light not only on their indeterminate category membership, but also on the degrees of grammaticalization of their various instantiations, as current research by each of the aforementioned authors suggests.…”
Section: Resultsmentioning
confidence: 96%
“…17 Dehé (2009) points out, against common assumptions about the prosody of parentheticals, that English comment clauses like I think have a variety of prosodic realizations. Although for this reason, prosodic integration and lack of pitch movement cannot serve as a strict definitional requirement for a construction to qualify as a particle, it should be noted that being phrased separately and carrying stress is not an uncommon prosodic profile for parentheticals while being much more marked for particles.…”
mentioning
confidence: 99%
“…I will not attempt to discuss here the complex characterization of the comma intonation, and I refer the reader to the existing literature, for instance the discussion in Dehé (2007 and2009) and Döring (2007). Recall also that there is a huge and very interesting literature on parentheticals, which I will not be able to consider in this work.…”
Section: 1 a Proposal For Parentheticalsmentioning
confidence: 99%